2016
DOI: 10.1136/jclinpath-2016-203995
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node yield is an independent predictor of survival in rectal cancer regardless of receipt of neoadjuvant therapy

Abstract: Suboptimal LNY is independently associated with worse overall survival regardless of neoadjuvant therapy, pathological staging and patient factors in rectal cancer. This finding underlies the importance and challenge of an optimal lymph node evaluation for prognostication, especially for patients receiving neoadjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 33 publications
3
35
1
Order By: Relevance
“…In our multivariate analysis, the number of harvested lymph nodes was one of the independent predictors of PFS. This finding was consistent with previous studies by Xu et al [28] and Wang et al [29].…”
Section: Discussionsupporting
confidence: 94%
“…In our multivariate analysis, the number of harvested lymph nodes was one of the independent predictors of PFS. This finding was consistent with previous studies by Xu et al [28] and Wang et al [29].…”
Section: Discussionsupporting
confidence: 94%
“…A low LNH in NACRT patients could either represent either poor oncological clearance and hence inadequate staging or a good response to NACRT and therefore a predictor of good outcome. While some studies show that LNH predicts worse overall survival regardless of NACRT [11,13], majority of the literature are proponents of the notion that a LNH metric may not be clinically relevant in the era of neoadjuvant therapy [9,12,17,18]. Our paper demonstrates that a LNH cut-off of 12 is not significantly associated with poorer DFS and OS in patients who received pre-operative NACRT.…”
Section: Discussionmentioning
confidence: 66%
“…Neoadjuvant chemoradiotherapy (NACRT) is known to decrease the lymph node harvest (LNH) in the resected specimen [3][4][5]. While studies have shown that LNH is associated with recurrence and survival in rectal cancer patients who have undergone upfront surgery [6,7], its prognostic value in patients who have received NACRT is debatable [8][9][10][11][12][13]. Although some studies show that LNH has no significant correlation with recurrence or survival in NACRT patients [9,12], some report that a suboptimal LNH of < 12 independently predicts worse overall survival irrespective of neoadjuvant treatment [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…We stated that patients with more LNs had a higher risk of LNM. In some surgical and pathological investigations, the LNs yielding or sampling indicated that the number of LNs in colorectal patients have drawn awareness . The previous study confirmed that in colorectal patients with only one metastatic LN, the 5‐year survival rate was significantly higher than those with greater than or equal to two LNs (67% to 39.6%) .…”
Section: Discussionmentioning
confidence: 88%
“…Morphological features and size of LNs were considered as possible manners to determine LNM. The number of LNs is valued in surgery and pathology, yet little attention has been paid to it on the MRI. Contrast‐enhanced MRI is not a mandatory choice to assess rectal cancer in staging; nevertheless, many approaches are trying to reveal its potential importance …”
Section: Introductionmentioning
confidence: 99%